Mycobacterium tuberculosis Alters the Metalloprotease Activity of the COP9 Signalosome - Lia Danelishvili (American Society for Microbiology, 2014)
ABSTRACT Inhibition of apoptotic death of macrophages by Mycobacterium tuberculosis represents an important mechanism of virulence that results in pathogen survival both in vitro and in vivo. To identify M. tuberculosis virulence determinants involved in the modulation of apoptosis, we previously screened a transposon bank of mutants in human macrophages, and an M. tuberculosis clone with a nonfunctional Rv3354 gene was identified as incompetent to suppress apoptosis. Here, we show that the Rv3354 gene encodes a protein kinase that is secreted within mononuclear phagocytic cells and is required for M. tuberculosis virulence. The Rv3354 effector targets the metalloprotease (JAMM) domain within subunit 5 of the COP9 signalosome (CSN5), resulting in suppression of apoptosis and in the destabilization of CSN function and regulatory cullin-RING ubiquitin E3 enzymatic activity. Our observation suggests that alteration of the metalloprotease activity of CSN by Rv3354 possibly prevents the ubiquitin-dependent proteolysis of M. tuberculosis-secreted proteins. IMPORTANCE Macrophage protein degradation is regulated by a protein complex called a signalosome. One of the signalosomes associated with activation of ubiquitin and protein labeling for degradation was found to interact with a secreted protein from M. tuberculosis, which binds to the complex and inactivates it. The interference with the ability to inactivate bacterial proteins secreted in the phagocyte cytosol may have crucial importance for bacterial survival within the phagocyte.